Positive Airway Cultures in Dogs and Cats Receiving Mechanical Ventilation for Tick Paralysis - Suzanne Suk Kwan Tso; Ellie Leister; Claire Rebecca Sharp; Jane Heller; Justine S. Gibson (Animals, 2022)
Animals with tick paralysis often require mechanical ventilation (MV) but previous publications have identified knowledge gaps regarding the development of bacterial pneumonia, and the specific pathogens involved. The objectives of this study were to describe the clinical course and culture and susceptibility profiles of bacteria isolated from airway samples of dogs and cats mechanically ventilated for tick paralysis that had positive airway cultures. Medical records were reviewed, and cases included if they had a positive airway sample culture during MV for tick paralysis. Twenty-four dogs and two cats were included. Most (85%) received empirical antimicrobials before airway sampling. The most common organisms isolated included Staphylococcus spp. (11), Klebsiella spp. (9), Enterococcus faecalis (8), Escherichia coli (6), Enterococcus faecium (3), Pseudomonas aeruginosa (4), and Mycoplasma spp. (3). Evidence of aspiration pneumonia was present in 22/25 (88%) cases that had thoracic radiographs performed. Seventy-seven percent of cases received antimicrobials to which the cultured bacteria were susceptible during hospitalisation. The median duration of MV was 4 days (range 1–10). Most (77%) survived to discharge, 19% were euthanised, and one died. In a multivariable logistic regression analysis it was identified that selection of antimicrobials to which the causative bacteria are susceptible was associated with survival to discharge (Odds ratio 45.8, p = 0.014; 95%CI 1.98–14,808), as was length of MV, with every day an animal is ventilated associated with a 4.7 times increased chance of survival (p = 0.015; 95% CI 1.21–78.4).